Upaya Kepala Sekolah dalam Mengatasi Guru yang Mengalami Masalah Metode Mengajar - Zainiyah Hayyi; Najmi Faza (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2022)
Supervision is a planned coaching in helping teachers and other staff in an effective work to achieve educational goals. The principal as a supervisor provides guidance and encouragement to teachers in the implementation of education and teaching, especially in terms of selecting learning methods. This research aim to describe: 1) How the principal’s efforts in dealing with teachers who has teaching method problems. 2) What are the supporting and inhibiting factors for the principal in overcoming teachers who has teaching method problems. This research method is descriptive qualitative research. The data were collected by interviews, observation, and documentation. Data analysis used qualitative descriptive techniques. In this case the researcher tries to understand the situation that occurs in MTs Raudlatul Ihsan on supervision. From the research results, the principal’s efforts in dealing teachers who has teaching method problems, namely managerial supervision, including providing facilities and infrastructure and reward and punishment, academic supervision, which includes conducting class visits or meetings and including teachers training. Supporting and inhibiting factors for the principal in dealing with teachers who has teaching methods, supporting factor : positive enthusiasm from the teachers. Inhibiting factors, internal: the amount of work and responsibility of the principal, external: lack of ability or competences of the teacher.